2023
DOI: 10.3390/fermentation9030218
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing Proteolytic Enzymes Increased the In Vitro Nutrient Effective Degradability and Fermentation Characteristics of Pineapple Waste Silage

Abstract: Pineapple waste silage (PAS) is an abundant agro-industrial by-product characterized by its high fiber content posing a high potential feed value as roughage for ruminants. Studies on its supplementation with proteolytic enzyme (PE) will help extend its utilization as an alternative nutritive feed source for cattle nutrition. Thus, this study aimed to determine the in vitro nutrient degradability and fermentation characteristics of fiber-rich but low-protein PAS supplemented with different levels of PE. Seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(31 reference statements)
0
0
1
Order By: Relevance
“…Afshar (2011) also conducted an in vitro rumen fermentation experiment using 3 cattle as rumen uid donors and apple residue as fermentation substrate, and their (a + b) values were lower than ours (263.67 vs. 77.82 mL), indicating that RRTR may be utilized more than apple residue for digestion. Margarette et al (2023). reported that supplementation with proteolytic enzymes increased the in vitro nutrient degradation and fermentation characteristics of pineapple waste silage and that the (c) value was 0.45%/h without the addition of enzymes, which is higher than that in our study.…”
Section: In Vitro Production and Dynamics Of Rrtrcontrasting
confidence: 84%
“…Afshar (2011) also conducted an in vitro rumen fermentation experiment using 3 cattle as rumen uid donors and apple residue as fermentation substrate, and their (a + b) values were lower than ours (263.67 vs. 77.82 mL), indicating that RRTR may be utilized more than apple residue for digestion. Margarette et al (2023). reported that supplementation with proteolytic enzymes increased the in vitro nutrient degradation and fermentation characteristics of pineapple waste silage and that the (c) value was 0.45%/h without the addition of enzymes, which is higher than that in our study.…”
Section: In Vitro Production and Dynamics Of Rrtrcontrasting
confidence: 84%